Healthcare-seeking Behaviour among the Tribal People of Bangladesh: Can the Current Health System Really Meet Their Needs? - Rahman, Syed Azizur; Kielmann, Tara; McPake, Barbara; Normand, Charles (Journal of Health, Population and Nutrition, 2012)
Despite the wealth of studies on health and healthcare-seeking behaviour among the Bengali population in Bangladesh, relatively few studies have focused specifically on the tribal groups in the country. This study aimed at exploring the context, reasons, and choices in patterns of healthcare-seeking behaviour of the hill tribal population of Bangladesh to present the obstacles and challenges faced in accessing healthcare provision in the tribal areas. Participatory tools and techniques, including focus-group discussions, in-depth interviews, and participant-observations, were used involving 218 men, women, adolescent boys, and girls belonging to nine different tribal communities in six districts. Data were transcribed and analyzed using the narrative analysis approach. The following four main findings emerged from the study, suggesting that the tribal communities may differ from the predominant Bengali population in their health needs and priorities: (a) Traditional healers are still very popular among the tribal population in Bangladesh; (b) Perceptions of the quality and manner of treatment and communication can override costs when it comes to provider-preference; (c) Gender and age play a role in making decisions in households in relation to health matters and treatment-seeking; and (d) Distinct differences exist among the tribal people concerning their knowledge on health, awareness, and treatment-seeking behaviour. The findings challenge the present service-delivery system that has largely been based on the needs and priorities of the plainland population. The present system needs to be reviewed carefully to include a broader approach that takes the sociocultural factors into account, if meaningful improvements are to be made in the health of the tribal people of Bangladesh. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12299 J HEALTH POPUL NUTR 2012 Sep;30(3):353-365